The Effect of Social Capital and Digital Literacy on Business Continuity at the Binong Jati Knitting Center, Bandung - Eka Ludya, Eka Ludya; Elis Dwiana Ratnamurni (CV. Inara, 2021)
The existence of MSMEs in Bandung has a high enough influence. Bandung City MSMEs contribute as much as 80 percent of Bandung City's GDP. Although small businesses have shown their role in the national economy, they still face various obstacles and constraints, both internal and external. (Tresnawati et al., 2019). (Abdullah, 2013) in his research explained that social capital as basic capital for the community can make capital and other potentials effective. The implementation of the strength of social capital is understood in its three typologies, namely social capital as the glue for community members, as a bridge and as a connection or access. To make MSMEs move up in class, a strategy is needed, one of which is the use of digital economic literacy. The development of digital-based MSMEs requires digital literacy so that when MSMEs are able to utilize digital technology it will increase acceptance by up to 80% (Erlanitasari, Rahmanto and Wijaya, 2020). This research is quantitative using multiple regression method. The population in this research is the business actors in Sentra Rajut Binong Jati Bandung. The results of this study can explain that social capital partially affects business sustainability. Business digital literacy variables partially affect business sustainability. As well as social capital and digital literacy simultaneously have an effect on business sustainability.